China and the World in the Liangzhu Era - Chen, Minghui. author. aut Link
XI, 204 p. 145 illus., 79 illus. in color.
Keywords: This book aims to portray ancient civilizations and the development of early states in China and the rest of the world during the Liangzhu period. From a global perspective, it describes the ancient Egyptian, Sumerian and Harappan civilizations, as well as lesser-known civilizations such as the Cyclades and Caral, underscoring the similarities and differences between their central settlements, capitals and material cultural remains. As for the national aspect, the book mainly explores the development process of east Asian civilization as represented by Chinese civilization and probes into the evolution of the Liangzhu, Dawenkou and Qujialing civilizations four to five thousand years ago in a search for the origins of Chinese civilization.